Surface structure of Pt/Si(001) - Choi, DS; Jung, JW; Shin, DS; Yoon, MS; Cho, WS; Kim, JY; Chae, KH; Jeong, KH; Whang, CN (ELSEVIER SCIENCE BV, 2002)
We have investigated Pt adsorption on the Si(001) surface using LEED and low energy ion scattering spectroscopy (ISS). We observe a c(4 x 2) LEED image at annealing temperatures between 700 and 1150 degreesC. For annealing temperatures between 800 and 1000 degreesC a c(4 x 6) LEED image is observed simultaneously with the c(4 x 2) LEED image. The Pt/Si(001) surface structure does not depend on the initial Pt coverage. We also measure the adsorption site at the c(4 x 2) surface using the ISS. We find that the Pt atoms are adsorbed at T3 sites and some Pt atoms diffuse into the bulk. The height of the adsorbed Pt atoms from the Si surface is determined to be 0.5 Angstrom. (C) 2002 Elsevier Science B,V. All rights reserved.
Keywords: INTERFACE